Konsep Filsafat Ilmu dalam Perspektif Islam dan Barat - Sumiran, Sumiran; Ummah, Kholifatul (TSAQOFAH, 2026)
Philosophy of science is a reflective inquiry into the nature, sources, methods, and purposes of knowledge, while developments in modern science reveal fundamental differences between Western and Islamic traditions in their views of knowledge. This article aims to examine the concept of philosophy of science from Islamic and Western perspectives and to analyse their similarities and differences. The study employs a qualitative method with a library research approach through critical review of relevant works on philosophy of science, Islamic epistemology, and the modern Western intellectual tradition. The findings show that modern Western philosophy of science tends to be grounded in rationalism, empiricism, and secularism, thereby separating knowledge from spiritual values and rendering it autonomous from revelation. In contrast, Islamic philosophy of science is founded on the principle of tauhid, which integrates revelation, reason, and moral values into a single, hierarchical, and mutually complementary unity. The article concludes that integrating the paradigm of Islamic philosophy of science offers an important alternative for responding to the value crisis in the development of modern science, while also opening space for the construction of knowledge that is more ethical, transcendental, and oriented toward human well-being.